2015
DOI: 10.3390/en9010007
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Wind Speed Prediction Based on a Self-Adaptive ARIMAX Model with an Exogenous WRF Simulation

Abstract: Abstract:Wind speed forecasting is difficult not only because of the influence of atmospheric dynamics but also for the impossibility of providing an accurate prediction with traditional statistical forecasting models that work by discovering an inner relationship within historical records. This paper develops a self-adaptive (SA) auto-regressive integrated moving average with exogenous variables (ARIMAX) model that is optimized very-short-term by the chaotic particle swarm optimization (CPSO) algorithm, known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Table 2. Estimated coefficients entering Equations (12a)-(12c) of the ARIMA processes describing the stochastic evolution of the coefficients in Equations (11) and (13). Notice that each coefficient is modelled with an ARIMA process of different order: ARIMA(3, 1, 1) for θ 1 , ARIMA(1, 1, 0) for θ 2 , and ARIMA(2, 1, 2) for ζ.…”
Section: Nested Arima Model For Wind Speedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2. Estimated coefficients entering Equations (12a)-(12c) of the ARIMA processes describing the stochastic evolution of the coefficients in Equations (11) and (13). Notice that each coefficient is modelled with an ARIMA process of different order: ARIMA(3, 1, 1) for θ 1 , ARIMA(1, 1, 0) for θ 2 , and ARIMA(2, 1, 2) for ζ.…”
Section: Nested Arima Model For Wind Speedsmentioning
confidence: 99%
“…Though using considerably more data, neural networks seem to guarantee improvements not better than 6%. ARIMA models with exogenous variables have been also developed [11] for modelling 15 min average wind speed. By studying wind speed series from China, it has been found that an ARIMA model combined with empirical mode decomposition has a better accuracy in comparison with neural networks and other machine learning approaches [12], achieving a mean absolute error smaller than 4%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With different developed forecasting approaches, Zhao, Zhao, Liu, Su and An [23] conducted a study to forecast wind speed using the self-adaptive auto-regressive integrated moving average chaotic particle swarm optimization (SA-ARIMA-CPSO) approach. This approach was developed by a SA auto-regressive integrated moving average, with an exogenous variables (ARIMAX) model, through the optimization of the CPSO algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has been a lot of work testing and improving various statistical correction methods in order to improve the forecast skill of NWPs [1]. Typical approaches include comparison and combination of different statistical models [11][12][13][14] and NWP datasets [15], and incorporating more input parameters.…”
Section: Introductionmentioning
confidence: 99%